Annotated list of island lady beetles from Chile (Coleoptera: Coccinellidae) - Gonzalez, Guillermo; Cotoras, Darko D.; Grez, Audrey A. (Zootaxa, 2020)
We provide a list of coccinellids (Coleoptera: Coccinellidae) species from the island territories of Chile. We report a total of 68 records, coming from ten islands, including 42 species corresponding to more than 35% of the species of the country. This paper presents the first Coccinellidae records for the Islas Desventuradas, Isla Mocha and Isla Tenglo. Contrary to what has been reported on other islands and other taxonomic groups in Chilean islands, the level of coccinellid endemism is low (8%), with only one and two species endemic to the Juan Fernández archipelago and Isla de Chiloé, respectively, and probably a fourth species from the Isla Grande de Tierra del Fuego. The presence of species with worldwide distribution and of agricultural relevance is strong in the Chilean oceanic islands, particularly in Rapa Nui. The fauna of the continental islands is very similar to the one in the nearby continental areas and composed of native species. Further surveys of Coccinellidae and other insects are required for the islands of Chile, especially for several of them in which there are no records.